2022
DOI: 10.3390/biomedicines10061226
|View full text |Cite
|
Sign up to set email alerts
|

Causative Agents of Ventilator-Associated Pneumonia and Resistance to Antibiotics in COVID-19 Patients: A Systematic Review

Abstract: Patients with coronavirus disease 2019 (COVID-19) have an increased risk of ventilator-associated pneumonia (VAP). This systematic review updates information on the causative agents of VAP and resistance to antibiotics in COVID-19 patients. We searched the Cochrane Central Register of Controlled Trials (CENTRAL), PubMed/MEDLINE, and LILACS databases from December 2019 to December 2021. Studies that described the frequency of causative pathogens associated with VAP and their antibiotic resistance patterns in cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 48 publications
1
6
0
1
Order By: Relevance
“…The most frequently isolated microorganisms during the COVID-19 period in our cohort were Gram-negative organisms (K. pneumoniae and Acinetobacter baumannii). This is similar to other studies, 25,28 including in the local setting, where K. pneumoniae was commonly isolated among COVID-19 patients admitted in a tertiary-level government hospital. 26 However, in our cohort, there was an increase in ESBL-producing K. pneumoniae during the COVID-19 period compared to the pre-COVID-19 period.…”
Section: Discussionsupporting
confidence: 91%
“…The most frequently isolated microorganisms during the COVID-19 period in our cohort were Gram-negative organisms (K. pneumoniae and Acinetobacter baumannii). This is similar to other studies, 25,28 including in the local setting, where K. pneumoniae was commonly isolated among COVID-19 patients admitted in a tertiary-level government hospital. 26 However, in our cohort, there was an increase in ESBL-producing K. pneumoniae during the COVID-19 period compared to the pre-COVID-19 period.…”
Section: Discussionsupporting
confidence: 91%
“…De Bruyn et al [51] also reported that a majority of COVID-19 patients had secondary bacterial infections during their hospital ICU stay. In a systematic review of ventilator-associated bacterial pneumonia among COVID-19 patients, Velásquez-Garcia et al [52] found that gram-negative bacteria were the most frequent causes of pneumonia with Staphylococcus aureus being the most common organism isolated among those patients.…”
Section: The Covid-19 Example With Bacterial And/or Fungal Infections...mentioning
confidence: 99%
“…These risk variables include advanced age, gender, prolonged MV, impaired consciousness, burns, the presence of comorbidities, previous antibiotic medication, invasive surgical procedures, and genetic polymorphisms [9]. Velásquez-Garcia et al (2022) proposed that the incidence, etiological agents, and patterns of antimicrobial resistance associated with VAP vary across surgical ICUs in Western countries and developing Asian nations [10]. The prevalence of resistant organisms in Thailand has seen a gradual upward trend over the last decade [11].…”
Section: Introductionmentioning
confidence: 99%